Genome-Wide Identification of Tannase Genes and Their Function of Wound Response and Astringent Substances Accumulation in Juglandaceae - Wang, Jianhua; Wang, Ketao; Lyu, Shiheng; Huang, Jianqin; Huang, Chunying; Xing, Yulin; Wang, Yige; Xu, Yifan; Li, Peipei; Hong, Junyan; Xi, Jianwei; Si, Xiaolin; et al. (Frontiers in Plant Science, 2021)
Tannins are important polyphenol compounds with different component proportion in different plant species. The plants in the Juglandaceae are rich in tannins, including condensed tannins and hydrolysable tannins. In this study, we identified 7 tannase genes (TAs) responsible for the tannins metabolism from walnut, pecan and Chinese hickory, three nut trees species in the Juglandaceae, which were divided into two groups. The phylogenetic and sequence analysis showed that TA genes and neighboring clade genes (TA-like genes) had similar sequences compared with other carboxylesterase genes, which may be the original of TA genes produced by tandem repeat. TA genes also indicated higher expressions in leaf than other tissues and were quickly up-regulated at 3 hours after leaf injury. During the development of the seed coat, the expression of the synthesis-related gene GGTs and the hydrolase gene TAs were continuously decreased, resulting in the decrease of tannin content in dry sample of seed coat of Chinese hickory. However, due to the reduction in water content during the ripening process, the tannins content in fresh sample increased, so the astringent taste was obvious at mature stage. In addition, the CcGGTs expression was higher than CiGGTs in initiation of development, but CcTAs continued down-regulated while CiTA2a and CiTA2b were up-regulated, which may bring about the significant differences in tannin content and astringent taste between Chinese hickory and pecan. These results proved the role of TAs in wound stress of leaves and astringent ingredients accumulation in seed coats of two nut trees species in the Juglandaceae.